Worldwide new host record of Sclerotinia sclerotiorum on Cannabis indica in Jammu, India (Journal of Oilseed Brassica, 2026)
Sclerotinia sclerotiorum (Lib.) de Bary, the causal organism of over 500 host plants is distributed worldwide, and it is among the most nonspecific, omnivorous and successful plant pathogen. On Cannabis indica stem, white mycelial growth bearing black, spherical to cylindrical sclerotia was observed. It was identified as Sclerotinia sclerotiorum (Lib.) de Bary. To the best of our knowledge, this is the worldwide new host record of Sclerotinia sclerotiorum.